Clinical Pearls in Medical Toxicology: Updates Ranging From Decontamination to Elimination. (June 2019) - Procopio, Gabrielle L.; Patel, Ruchi; Gupta, Amit
Such as any field of medicine, it is imperative to stay current with the latest advances and treatment modalities in toxicology. With the absence of rigorous randomized controlled trials, many updated guidelines are created by expert consensus and/or case reports and clinical experience. Over the past 10 years, there have been several changes in the management of drug overdoses in light of new data available. Although this is not a comprehensive review of all available antidotes, this article will focus on several important interventions including the use of gastrointestinal decontamination, hyperinsulinemic–euglycemic therapy, methylene blue, intravenous lipid emulsion, hemodialysis, and extracorporeal membrane oxygenation.